Enforcement of foreign judgment in e-commerce consumer contracts in Malaysia: Issues and challenges / Shazanah Sarwar Khan and Sheela Jayabalan - Sarwar Khan, Shazanah; Jayabalan, Sheela (Penerbit UiTM (UiTM Press), 2015)
Electronic commerce or e-commerce is gaining momentum in Malaysia. Consumers are finding transacting online to be a convenient method especially to buy goods and services. As online transactions involve transborder commerce, disputes are inevitable. As such the question of conflict of laws arises, one of which involves enforcement of foreign judgement. Even though there is a law regulating enforcement of foreign judgement in Malaysia, however it does not take into consideration consumer protection. Adapting doctrinal research, this article discusses issues and challenges arising in the enforcement of foreign judgement in e-commerce consumer contracts in Malaysia